Determinação da concentração inibitória mínima de óleos essenciais de Lippia origanoides Kunth tratados com diferentes reguladores de metabolismo vegetal - Vieira, Lara Raisa Cheles (2014)
The use of plant extracts and phytochemicals with medicinal purpose is one of the oldest forms of medical applications of humanity, and currently, the use of herbal medicines has increased in population. Considering the popular use of Lippia origanoides in the treatment of respiratory and gastrointestinal diseases and antiseptic action of its essential oil, this study aimed to test, through of the Minimum Inhibitory Concentration and Minimum Microbicidal Concentration, the antimicrobial activity of the essential oils of L. origanoides resulting from plants after treatment with plant metabolism regulators: acetylsalicylic acid, jasmonic acid, 6-benzylaminopurine, gibberellic acid, Stimulate ® and distilled water (control), continuing earlier work by our group. The results for the antimicrobial activity of the studied species varied according to the treatment received, collection period and the microorganism tested. In general, the 12 essential oils tested showed activity against the seven test microorganisms used. Oils resulting from treatment with acetylsalicylic acid, jasmonic acid and gibberellic acid had significantly lower MIC values, highlighting their high efficacy; being evident that the time for collecting the samples interfered in these results. The oil resulting from the first collection of plants were in general more efficient than the third. There was significant difference between the MIC values for strains of C. albicans CCMB 266 and CCMB 286, the latter being more sensitive to the oils from both collection periods.